A TC/WMS-TDLAS mid-infrared detection method for ultra-low concentration carbon isotope methane. Issue 12 (7th November 2022) - Wang, Bin; Tang, Xiaojun; Gan, Yuanying; Li, Xiaoshan; Lu, Youshui
Abstract : In this study, a TC/WMS-TDLAS detection method for carbon isotope methane is proposed. By controlling the operating temperature of the laser source and the gas cell, the measurement of ultra-low concentration carbon isotope methane was achieved. Abstract : There is a great demand for online high-precision monitoring of carbon isotope methane in the fields of atmospheric monitoring, geological exploration, oil and natural gas extraction, etc. However, the current detection method has some problems, such as the difficulty to ensure a wide concentration detection range while detecting an ultra-low concentration of carbon isotope methane with high accuracy, and a long detection period. To address these issues, in this paper, we propose TC/WMS-TDLAS, temperature-controlled/wavelength-modulated spectroscopy of tunable diode laser absorption spectrometry for the detection of ultra-low concentration carbon isotope methane. Also, we analyze the effect of temperature variation on the absorption signal of the infrared spectrum of carbon isotope methane and further investigate the interaction effect of the two isotope detection when the concentrations of 12 CH4 and 13 CH4 differed greatly. In addition, we develop a calibration model for detection when the difference between 12 CH4 and 13 CH4 concentrations is large. The experimental results show that TC/WMS-TDLAS can achieve an efficient analysis of 12 CH4 and 13 CH4 concentrations when the gas volume is less than 200 mL with a detection period less than 2 s. The detection error for ultra-low concentration carbon isotope methane is less than 1%, and the lower limit of detection for the concentration of 12 CH4 and 13 CH4 is 0.5 × 10 −6 (0.5 ppmv) and 0.1 × 10 −6 (0.1 ppmv), respectively. It also demonstrates that TC/WMS-TDLAS has significantly improved the detection performance of TDLAS for ultra-low concentration carbon isotope methane and it is promising for future application.